Bullying in Maldives: effects on adolescents mental health - Nasheeda, Aishath; Che Hassan, Norlizah; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The purpose of this paper is to develop a conceptual framework based on extensive literature review on bullying in Maldives and effects on adolescents’ mental health. This study is based on biopsychosocial model of development. It explores the relationship between biological and social changes that take place during adolescences and the role in individual functioning with regard to promoting health and causing illnesses. Based on literature review, bullying is conceputalized as repeated intentional exposure to physical, verbal and relational/social harassment. Well-being of health that may be affected by bullying were identified as (a) anxiety, (b) Depression (c) Loss of behavioural / Emotional control (d) General Positive Affect (e) Emotional Ties (f) Life satisfaction. Further research may lead to understanding of why some children do not report or stand up to being bullied, why some children bully others and why some bystanders do not report bullying incidences. The research yields a theoretical understanding of how biology, psychology and social environment interact in bullying scenarios. This will facilitate in developing bullying framework and intervention strategies.